Food supply chains - Zhou, Qian (2011)
The dissertation analyses food waste in global supply chain. From the related managerial literature, the process of supply chain operation, from agriculture, manufacturing, warehouses, retailers to customers are explained clearly. Then the reasons and characteristics of food wastes in any point of food supply chain are analyzed. From some case studies and questionnaire investigation, some corresponding methods to reduce food waste are put forward in the following. Lastly, in terms of method selection, the evaluation with advantages and disadvantages of each method and a quantitative calculation facilitate food waste reduction strategies establishment in practices.